ANALISIS DAN PERANCANGAN KEAMANAN DATA TEKS MENGGUNAKAN ALGORITMA KRIPTOGRAFI SECURE HASH ALGORITHM - Suhendra, Irwan; Andi Maslan (Computer Science and Industrial Engineering, 2024)
Data security is a crucial aspect in today's digital era, especially with the increasing exchange of information over the network, so network security seeks to secure from physical and logical dangers and threats that can steal personal data. This research aims to analyse and design a text data security system by utilising the Secure Hash Algorithm (SHA) cryptographic algorithm in order to increase the level of security and integrity of text data through the application of reliable cryptographic technology. The research method used is Secure Hash Algorithm (SHA) 256 to analyse text data, and later the text data will be processed using the SHA 256 application to find out how it works and its implementation on securing text data. The results for how SHA works have a predetermined initial value for each hash literacy generated from several prime numbers, the message to be hashed is divided into smaller blocks, each of which has a length of 512 bits and padding is done so that the length of the text can be divided by 512 which later for each text block is processed repeatedly for 64 rounds, after all text blocks are processed, the resulting hash value is a series of bits with a certain length. The results for the SHA implementation steps are first to take the text data to be secured, then convert the text data into ASCII/Unicode format, run the SHA algorithm to find the hash value, save the hash value into the database, then verify the authenticity of the text data, run the SHA algorithm on the data and compare the hash value generated with the hash value previously stored, if the result is the same, then the text data is original. Recommendations that can be given are to explore and develop the blockhchain side and improve the SHA 256 application in the testing section.fritzing.